Hydrogen bond interactions of coumarin-153 in molecular solvents: molecular dynamics and principal component analysis - Goloviznina, Kateryna; Dudariev, Dmytro; Miannay, François-Alexandre; Kalugin, Oleg; Koverga, Volodymyr; Takamuku, Toshiyuki; Vitale, Raffaele; Idrissi, Abdenacer (Comptes Rendus. Chimie)
Hydrogen bond interactions significantly affect the coumarin-153’s (C153) photophysics, including its ability to act as a donor of weak hydrogen bonds via its 14 C–H bonds and as an acceptor via its O atoms in the ester and the carbonyl groups, as well as via its F atom in the trifluoromethyl group. The distances between the donor atoms and their closest electronegative neighbor atom served as descriptors of the hydrogen bond interactions. These descriptors were calculated using the nearest neighbor radial distribution approach. Principal component analysis (PCA) was then performed on these distances to compare the unique structures surrounding donor bond atoms and identify patterns in the interactions between C153 and various solvent, such as acetonitrile, butyrolactone, propylene carbonate, methanol, ethanol, propanol, and butanol.Our findings demonstrate that, when C153 acts as a hydrogen bond donor, the interaction behavior of the H atoms that are close to the N atom and that of the H atom close to the trifluoromethyl F atom of C153 is substantially different. More specifically, the former H atoms interact preferentially with the hydroxyl oxygen atom of the solvent while the H$_{10}$ atom interacts preferentially with the ester oxygen atoms of propylene carbonate.Moreover, when C153 behaves as a hydrogen bond acceptor, PCA shows that the carbonyl O atom of C153 interacts preferentially with the hydroxyl H atom of the alcohols, while the F atoms mostly interact with the other ethyl and methyl H atoms of the solvent.